Knowledge sharing among academicians: The role of the big five personality traits / Arenawati Sehat Omar and Shahren Ahmad Zaidi Adruce - Omar, Arenawati Sehat; Zaidi Adruce, Shahren Ahmad (Universiti Teknologi MARA, Kedah, 2019)
Majority of the organizations invest large part of their resources in enhancing the employees’ knowledge, having recognised the importance of knowledge to their establishment. However, it is a challenging task to get those same employees to share their knowledge and experience. Therefore, present study aims to expand the understanding of the influence of the Big-Five personality (BFP) dimensions of an individual’s knowledgesharing behaviour. The study has provided evidences that the knowledge sharing behaviour is significantly influenced by the characteristics and personality traits of the individuals. The personality trait within the individual characteristics, is an important psychological factor that guides the individuals’ behaviour. The present study has enhanced the understanding of the relationship between personality and knowledge sharing. The study results are significant to guide researchers with hopes that it will enhance their understanding on knowledge sharing in the organizations, particularly the influence of personality trait dimensions on individuals’ knowledge-sharing behaviour.